Palgrave Advances in Irish History
XI, 296 p.
Keywords: This book provides a much-needed historiographical overview of modern Irish History, which is often written mainly from a socio-political perspective. This guide offers a comprehensive account of Irish History in its manifold aspects such as family, famine, labour, institutional, women, cultural, art, identity and migration histories.